Prenatal exposure of rats to nicotine causes persistent alterations of nicotinic cholinergic receptors - Gold, Allison B. (2008)
We examined for immediate and persistent changes in nAChRs in cerebral cortex, thalamus and striatum of male rats caused by prenatal exposure to nicotine from gestational day 3 to postnatal day 10 (PN10), and how such exposure affected the responses of adolescents to subsequent nicotine challenge. Receptor numbers were assessed by [(3)H]epibatidine binding and receptor function was measured by acetylcholine-stimulated (86)Rb efflux (cerebral cortex and thalamus) and nicotine-stimulated dopamine release (striatum). Immediate effects of prenatal nicotine, assessed in PN10 animals, were not detected for any parameter. A subsequent 14 day nicotine exposure in adolescence revealed persistent changes caused by prenatal nicotine exposure. Nicotine exposure in adolescents caused up-regulation of binding in all three regions; however, this up-regulation was lost in thalamus from animals prenatally exposed to nicotine. Nicotine exposure in adolescents caused decreased nicotine-stimulated dopamine release in striatum; this effect was also lost in animals prenatally exposed to nicotine. Comparison of parameters in PN10 and PN42 rats revealed developmental changes in the CNS cholinergic system. In thalamus, binding increased with age, as did the proportion of (86)Rb efflux with high sensitivity to acetylcholine. In cortex, binding also increased with age, but there was no change in total (86)Rb efflux, and the proportion of high to low sensitivity efflux declined with age. Nicotine-stimulated striatal dopamine release (both total and α-conotoxin MII-resistant release) increased with age in naïve animals, but not in those prenatally exposed to nicotine. These findings demonstrate that prenatal exposure to nicotine causes alterations in the regulation of nAChRs by nicotine that persist into adolescence. These changes may play a role in the increased risk for nicotine addiction observed in adolescent offspring of smoking mothers.